Association of Liver Enzymes with Thyroid Hormone Levels in Hyperthyroid Patients: A Cross-Sectional Study from a Tertiary Care Hospital: Association of Liver Enzymes with Thyroid Hormone Levels in Hyperthyroid Patients - Javaid, Faiza; Khan, Ahmad Raza; Sherwani, Hamza Khan; Rasheed, Asma; Sadiq, Maleeha; Asif, Isra (Pakistan Journal of Health Sciences, 2025)
Hyperthyroidism, characterized by the overproduction of thyroid hormones, may impact liver function. Understanding this relationship is essential for early identification and management of liver dysfunction in hyperthyroid patients. Objectives: To determine the association between thyroid hormone levels (TSH, T3, T4) and liver function tests (ALT, AST, ALP, bilirubin, and total protein) in patients with hyperthyroidism. Methods: This cross-sectional study was conducted from 28 July 2023 to 28 January 2024 at the Endocrinology OPD of Gulab Devi Hospital, Lahore. A total of 100 hyperthyroid patients were selected using non-probability sampling. Demographic data, thyroid profiles (T3, T4, TSH), and liver function tests (LFTs) were recorded. Data were analyzed by SPSS version 26.0 using descriptive statistics and Chi-square tests to assess associations. Results: Out of 100 hyperthyroid patients, 59 were female and 41 were male, with a mean age of 38.5 + 10.2 years. Elevated ALT was observed in 27% of patients, AST in 13%, ALP in 23%, bilirubin in 13%, and total protein in 11%. Chi-square analysis showed significant associations between TSH and ALT (p=0.028) and AST (p=0.017), as well as between T3 and ALP (p=0.031). No significant associations were found between T4 and any of the liver enzymes. Conclusions: A significant proportion of hyperthyroid patients showed abnormal LFTs, indicating a relationship between thyroid dysfunction and hepatic involvement. Further large-scale studies are recommended